Association of Tumor Markers with Total Testosterone in the Serum of Women with Polycystic Ovary Syndrome - Jinghua Zhang; Manman Pan; Qing Zhang; Fangfang Wang; Fan Qu (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: To investigate the correlations between serum levels of tumor markers [including carbohydrate antigen 125 (CA125), carcino-embryonic antigen (CEA) and alpha fetoprotein (AFP)] and the total testosterone of the patients with polycystic ovary syndrome (PCOS). Methods: The data was collected from 890 healthy Chinese women and 480 women with PCOS, including serum total testosterone (TTE), follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), progesterone (PGN), prolactin (PRL), CA125, AFP and CEA. The serum levels of reproductive hormone and tumor markers in the women with PCOS were compared among the subgroups in accordance with the classification of TTE quartiles. To further explore the association between CA125, AFP, CEA and the TTE levels, Spearman correlation analysis was performed. Results: PCOS had significantly lower CA125, and higher AFP and CEA levels in the serum than the healthy controls (p = 0.000, p = 0.015 and p = 0.001, respectively). Four subgroups divided by TTE showed significant differences in CA125 levels (p = 0.017). The Spearman correlation analysis also showed that CA125 was significantly negatively associated with serum TTE levels (p = 0.022). Conclusions: The serum level of CA125 is significantly lower and significantly correlated to the hormonal status of PCOS. AFP and CEA are significantly higher in PCOS.